PEDAGOGIC AND PROFESSIONAL COMPETENCIES IN S1 MATHEMATICS EDUCATION STUDENTS AS PROSPECTIVE HIGH SCHOOL MATHEMATICS EDUCATORS - Nadia Putri M. Posangi; Sintha Sih Dewanti; Said Subhan Posangi (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to identify the extent to which S1 Mathematics Education students have pedagogic and professional competencies that are in accordance with educator standards. Pedagogic and professional competencies are the two main components that must be possessed by prospective educators in order to carry out their duties optimally. This study uses a quantitative approach with a descriptive method with the research subject consisting of 110 students of the Mathematics Education Study Program consisting of 3 classes with different lecturers. The data collection technique used in this study is in the form of a test, the test used is in the form of an objective test in the form of multiple choice to gain a deep understanding of pedagogic and professional competence. The results of this study were obtained, the pedagogic competence of S1 students of the mathematics education study program as prospective educators was 80.12 with a good category. The highest score for students' pedagogic competence is found in the aspects of classroom management and effective assessment. Meanwhile, the professional competency score of S1 students of the mathematics education study program as prospective educators is 80.42 with a good category. The highest score for student professional competence is found in indicators using algebraic concepts and using patterns and functions with very good scores. The conclusion of this study is that the pedagogic and professional competence in S1 mathematics education students as prospective educators is classified as a good category.